Pengendalian Persediaan Primary Items dalam Logistik Konstruksi - Lady Lisya; Rika Ampuh Hadiguna (Jurnal Optimasi Sistem Industri, 2016)
Construction logistics are activities that consist of ordering, storage and transportation of materials of construction projects. Storage material is logistics activity that ensure the availability of materials in project site. Generally, material storage activities have been conducted at the project site. Logistics construction is aimed to support the project activities that the completion schedule has been set. Construction logistics issues is determining the schedule of ordering materials so that the project can be implemented on schedule. The purpose of research is to determine the optimum ordering period for the primary items on the main building structure construction and designing inventory control cards as a mechanism for monitoring procurement of materials. This research has been obtained optimal ordering period for the primary items of main building structure with elements of the work using Fixed Period Requirement method. Inventories were already meet the material requirement of each period. Material management has been conducted based grouping approach as many as 31 groups. In addition, this research has proposed the inventory control cards as an instrument for material procurement monitoring. The implications of inventory control cards are coordinate contracting parties with vendors to plan the replenishment of materials to meet the work schedule. Further research can be developed with other aspects such as integrated material order system between contractors and vendors to consider the safety stock. In addition, the information system for planning material is an important consideration for construction projects with large scale so that the companies can plan primary items inventory and other materials in the projects completion more easily, quickly and accurately.